Exploration, Analysis of Zinc (Zn) And Iron (Fe) Content in Local Rice Genotypes from West Sumatra: An Initial Step toward Biofortification for Stunting Mitigation - G Gustian; PK Dewi Hayati; Ryan Budi Setiawan; I Imelinda; Adhira Prameswari Ranayudha (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2024)
Stunting in children under five remains a significant public health issue in Indonesia, particularly in West Sumatra, where prevalence rates exceed the national average. Addressing this challenge requires improving nutritional intake, focusing on essential micronutrients like zinc (Zn) and iron (Fe). Biofortification is a promising agricultural strategy to enhance the nutritional quality of staple crops such as rice. This study aims to explore and evaluate the Zn and Fe content of local rice genotypes from West Sumatra, which hold potential for biofortification programs.Twenty-eight rice genotypes, including 27 local genotypes and one control (Inpari Nutri Zinc), were analyzed for Zn and Fe content. The results showed that the control variety, Inpari Nutri Zinc, exhibited the highest Zn (31.30 ppm) and Fe (19.85 ppm) content. Among the local genotypes, Puluik Mutia (Zn: 28.40 ppm, Fe: 18.30 ppm), Kuning Aro (Zn: 27.60 ppm, Fe: 18.20 ppm), and Rampai Kuning (Zn: 26.20 ppm, Fe: 18.05 ppm) displayed the highest Zn levels, while Manggung (Fe: 18.85 ppm) had the highest Fe content. These findings highlight the significant variability in micronutrient content among local genotypes, emphasizing their potential as germplasm for biofortification breeding programs.This research represents the first systematic exploration of Zn and Fe levels in local rice genotypes from West Sumatra. The novelty lies in identifying high-Zn and Fe genotypes, particularly those with firm texture preferences, which could support biofortification efforts and provide a sustainable solution to combat stunting. Future research should focus on environmental interactions and agronomic practices to further optimize the micronutrient content in local rice varieties